PRODUCTION of THERMAL PHOTONS IN VISCOUS FLUID DYNAMICS WITH TEMPERATURE-DEPENDENT SHEAR VISCOSITY - Peralta-Ramos, J. [UNESP]; Nakwacki, M. S. (World Scientific Publ Co Pte Ltd, 2012)
We compute the spectrum of thermal photons created in Au+Au collisions at root(NN)-N-s = 200 GeV, taking into account dissipative corrections in production processes corresponding to the quark-gluon plasma and hadronic phases. To describe the evolution of the fireball, we use a viscous fluid dynamic model with different parametrizat ions for the temperature-dependence of eta/s. We find that the spectrum significantly depends on the values of eta/s in the QGP phase, and is almost insensitive to the values in the hadronic phase. We also compare the influence of the temperature-dependence of eta/s on the spectrum of thermal photons to that of using different equations of state in the fluid dynamic simulations, finding that both effects are of the same order of magnitude.
Keywords: Relativistic viscous hydrodynamics; thermal photons; shear viscosity